IDNLearn.com provides a collaborative environment for finding and sharing answers. Discover comprehensive answers to your questions from our community of knowledgeable experts.
Sagot :
To solve the equation [tex]\(12^{x^2 + 5x - 4} = 12^{2x + 6}\)[/tex], we start by recognizing that the bases on both sides are the same. This allows us to set the exponents equal to each other:
[tex]\[ x^2 + 5x - 4 = 2x + 6 \][/tex]
Next, we rearrange the equation to form a standard quadratic equation by moving all terms to one side:
[tex]\[ x^2 + 5x - 4 - 2x - 6 = 0 \][/tex]
Simplify the equation:
[tex]\[ x^2 + 3x - 10 = 0 \][/tex]
Now that we have a quadratic equation, we can solve it using the quadratic formula, which is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For our equation [tex]\( x^2 + 3x - 10 = 0 \)[/tex], the coefficients are:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = -10\)[/tex]
First, calculate the discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac = 3^2 - 4(1)(-10) = 9 + 40 = 49 \][/tex]
Since the discriminant is positive, we will have two real solutions. We now substitute the values into the quadratic formula:
[tex]\[ x = \frac{-3 \pm \sqrt{49}}{2(1)} = \frac{-3 \pm 7}{2} \][/tex]
This gives us two solutions:
1. [tex]\( x_1 = \frac{-3 + 7}{2} = \frac{4}{2} = 2 \)[/tex]
2. [tex]\( x_2 = \frac{-3 - 7}{2} = \frac{-10}{2} = -5 \)[/tex]
Therefore, the solutions to the equation are:
[tex]\[ x = 2 \quad \text{and} \quad x = -5 \][/tex]
So, the correct answers are [tex]\( x = 2 \)[/tex] and [tex]\( x = -5 \)[/tex].
[tex]\[ x^2 + 5x - 4 = 2x + 6 \][/tex]
Next, we rearrange the equation to form a standard quadratic equation by moving all terms to one side:
[tex]\[ x^2 + 5x - 4 - 2x - 6 = 0 \][/tex]
Simplify the equation:
[tex]\[ x^2 + 3x - 10 = 0 \][/tex]
Now that we have a quadratic equation, we can solve it using the quadratic formula, which is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For our equation [tex]\( x^2 + 3x - 10 = 0 \)[/tex], the coefficients are:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = -10\)[/tex]
First, calculate the discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac = 3^2 - 4(1)(-10) = 9 + 40 = 49 \][/tex]
Since the discriminant is positive, we will have two real solutions. We now substitute the values into the quadratic formula:
[tex]\[ x = \frac{-3 \pm \sqrt{49}}{2(1)} = \frac{-3 \pm 7}{2} \][/tex]
This gives us two solutions:
1. [tex]\( x_1 = \frac{-3 + 7}{2} = \frac{4}{2} = 2 \)[/tex]
2. [tex]\( x_2 = \frac{-3 - 7}{2} = \frac{-10}{2} = -5 \)[/tex]
Therefore, the solutions to the equation are:
[tex]\[ x = 2 \quad \text{and} \quad x = -5 \][/tex]
So, the correct answers are [tex]\( x = 2 \)[/tex] and [tex]\( x = -5 \)[/tex].
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Find clear answers at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.